Ãrna saga biskups / Kafka / Bureaucracy / Desire - Cole, Richard (Collegium Medievale, 2016)
"Where one believed there was law, there is in fact desire and desire alone" - so wrote the philosophers Gilles Deleuze and Félix Guattari in their groundbreaking assault on the work of Franz Kafka, Kafka: Towards a Minor Literature. Deleuze and Guattari expose the exploitative power-plays and the sometimes awe-inspiring (sometimes grubby) workings of desire in moments which superficially appear to be sombrely official or legalistic. Ãrna saga biskups, an early fourteenth century saga concerning the life of Bishop Ãrni Þorláksson, readily presents itself for reconsideration through this theoretical lens. Often dismissed as dull and unfinished, the saga actually contains many episodes of narrative deftness and moving drama. In this article, attention is focused upon the narrative voice's ambivalence towards Bishop Ãrni, the bishop's essentially bureaucratic aspirations, and the merit of Ãrna saga biskups not only as a historical source, but as a literary triumph.